The Effects of in Situ-Formed Silver Nanoparticles on the Electrical Properties of Epoxy Resin Filled with Silver Nanowires - Song, Gwang-Seok (Polymers (Basel), 2016)
A novel method for preparing epoxy/silver nanocomposites was developed via the in situ formation of silver nanoparticles (AgNPs) within the epoxy resin matrix while using silver nanowires (AgNWs) as a conductive filler. The silver–imidazole complex was synthesized from silver acetate (AgAc) and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole (imidazole). AgNPs were generated in situ during the curing of the epoxy resin through the thermal decomposition of the AgAc–imidazole complex, which was capable of reducing Ag(+) to Ag by itself. The released imidazole acted as a catalyst to cure the epoxy. Additionally, after the curing process, the in situ-generated AgNPs were stabilized by the formed epoxy network. Therefore, by using the thermal decomposition method, uniformly dispersed AgNPs of approximately 100 nm were formed in situ in the epoxy matrix filled with AgNWs. It was observed that the nanocomposites containing in situ-formed AgNPs exhibited isotropic electrical properties in the epoxy resins in the presence of AgNWs.